2022
DOI: 10.3390/vaccines10122019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Immune Responses Following COVID-19 Infection and Vaccinations in Pregnancy

Abstract: The objective of the study was to compare the maternal and neonatal humoral immune responses among different groups of women, namely those vaccinated by the BNT162b2 vaccine, not vaccinated, and COVID-19-recovered parturient women at the time of delivery. This is a prospective cohort study of pregnant women, divided into four groups: Group A “Recovered”—recovered and not vaccinated. Group B “Second Vaccination”—first and second doses only. Group C “Third Vaccination”—third dose. Group D “No Third Vaccination”—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As reported to this day, vaccination received during pregnancy - also during the Omicron predominant period - increases the protection of infants aged 0 to 6 months, which is reflected in reduced risk of SARS-CoV-2 infection, infection-associated hospitalization, and morbidity ( 40 45 ). The effectiveness of such protection depends on the number of received vaccine doses, which was confirmed by the highest level of SARS-CoV-2-specific IgG antibodies in fully vaccinated pregnant and their offspring when compared to different groups of nonvaccinated, vaccinated, and infected parturient women ( 46 ). When discussing the importance of maternal vaccinations for the health of neonates, we should also remember about role of parental vaccinations in the indirect protection of newborns and older children sharing the same household ( 45 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 94%
“…As reported to this day, vaccination received during pregnancy - also during the Omicron predominant period - increases the protection of infants aged 0 to 6 months, which is reflected in reduced risk of SARS-CoV-2 infection, infection-associated hospitalization, and morbidity ( 40 45 ). The effectiveness of such protection depends on the number of received vaccine doses, which was confirmed by the highest level of SARS-CoV-2-specific IgG antibodies in fully vaccinated pregnant and their offspring when compared to different groups of nonvaccinated, vaccinated, and infected parturient women ( 46 ). When discussing the importance of maternal vaccinations for the health of neonates, we should also remember about role of parental vaccinations in the indirect protection of newborns and older children sharing the same household ( 45 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 94%
“…Hence, information related to the anti-viral vaccination and the viral infection—remains crucial. Studies have shown that maternal vaccination effectively protects pregnant women, their fetuses, and newborns from becoming infected 8 , 11 . Extensive studies support the importance of vaccination of gravid subjects before and during pregnancy and have confirmed its efficacy in reducing the rate of infection and protecting them from severe symptoms 21 .…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines were published soon after the vaccine became available in the country. Several reports showed a high rate of vaccination among pregnant women compared to other countries 8 . Extensive proactive efforts by medical staff to explain the safety of the vaccine to their patients and evidence of infant protection by vaccination were major drivers for vaccine acceptance 9 .…”
mentioning
confidence: 97%
“…COVID-19 during pregnancy is associated with adverse pregnancy and neonatal outcomes ( 1 ). Transplacental transfer of vaccine-induced SARS-CoV-2–specific antibodies has been demonstrated, and severe clinical infant outcomes related to COVID-19 are preventable through maternal vaccination ( 2 , 3 ). Effectiveness of maternal vaccination against COVID-19–related hospitalization (vaccine effectiveness [VE]) among infants aged <6 months was previously estimated to be 38% for infants hospitalized during the period of the SARS-CoV-2 Omicron variant predominance (December 2021–March 2022) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%